2019
DOI: 10.1073/pnas.1904602116
|View full text |Cite
|
Sign up to set email alerts
|

The constrained architecture of mammalian Hox gene clusters

Abstract: In many animal species with a bilateral symmetry, Hox genes are clustered either at one or at several genomic loci. This organization has a functional relevance, as the transcriptional control applied to each gene depends upon its relative position within the gene cluster. It was previously noted that vertebrate Hox clusters display a much higher level of genomic organization than their invertebrate counterparts. The former are always more compact than the latter, they are generally devoid of repeats and of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…This analysis has also revealed that NUP153 associates with several Hox genes, which are characterized as bivalent genes in mouse ES cells 1,48 . Genomic organization of the Hox loci relies on TADs with enriched CTCF binding 44 and influences developmental expression of Hox genes 49 . As presented in the representative tracks shown for the HoxA and HoxC clusters, we found that NUP153 depletion resulted in altered CTCF and/or cohesin binding at specific Hox genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis has also revealed that NUP153 associates with several Hox genes, which are characterized as bivalent genes in mouse ES cells 1,48 . Genomic organization of the Hox loci relies on TADs with enriched CTCF binding 44 and influences developmental expression of Hox genes 49 . As presented in the representative tracks shown for the HoxA and HoxC clusters, we found that NUP153 depletion resulted in altered CTCF and/or cohesin binding at specific Hox genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of TADs has been accompanied by increased clustering of coexpressed developmentally related genes, allowing these syntenic blocks to be regulated as a unit (Heger et al, 2012). Vertebrates, for example, exhibit clustering of Hox genes (Darbellay et al, 2019); however, by the time of origin of hemichordates, four transcription factor genes (nkx2.1, nkx2.2, pax1/9 and foxA) had assembled into a microsyntenic group (the pharyngeal cluster) controlling development of the pharyngeal 'gill' slits (Simakov et al, 2015).…”
Section: Box 2 Co-option and The Cambrian Explosionmentioning
confidence: 99%
“…While such negative ground-state structures may simply reflect the absence of upstream factors and/or represent a scaffold to reinforce future enhancer-promoter contacts (Paliou et al, 2019), it may in our case be functionally required to prevent any transcriptional leakage of Hoxd13. HOX13 products are indeed potent dominant negative proteins (Darbellay et al, 2019;Villavicencio-Lorini et al, 2010) and their ectopic production in time and space must be prevented for proper development to be achieved (e.g. (Young et al, 2009).…”
Section: Switching the Tad On And Off To Prevent Regulatory Leakagesmentioning
confidence: 99%